Home Automation using Raspberry PI (Global Journals of Research in Engineering, 2023)
The home automation system based on the Raspberry Pi and Node MCU leverages house hold appliances and allows users to control them vi the internet from anywhere in the globe It enables control and operation of appliances and gadgets in a house through communication between hardware and software Home automation might lead to more effective and intelligent energy saving strategies The main goal of this project is to build a home automation system using a Raspberry Pi and a Node MCU board with the internet controlled by the Telegram application With the Io idea all household appliances and electrical equipment may be regulated automatically as well as manually via relay circuits